Accelerated epigenetic aging mediates link between adverse childhood experiences and depressive symptoms in older adults: Results from the Health and Retirement Study - Eric T. Klopack; Eileen M. Crimmins; Steve W. Cole; Teresa E. Seeman; Judith E. Carroll (Elsevier, 2022)
Adverse childhood experiences (ACEs) increase risk for depression at subsequent ages and have been linked to accelerated biological aging. We hypothesize that accelerated epigenetic aging may partially mediate the link between ACEs and depression. This study examines 3 three second/third-generation epigenetic aging measures (viz., GrimAge, PhenoAge, and DunedinPoAm38) as mediators of the link between ACEs and depressive symptoms in older adulthood. We utilize structural equation modeling to assess mediation in the Health and Retirement Study (N = 2672). Experiencing ACEs is significantly associated with an older GrimAge and a faster pace of aging via the DunedinPoAm38. Having an older GrimAge and faster DunedinPoAm38 pace of aging were also significantly associated with more depressive symptoms. PhenoAge was not significantly associated with depressive symptoms and was only associated with experiencing three ACEs. These associations were reduced by socioeconomic and lifestyle factors, including obesity and substance use. GrimAge explained between 9 and 14% of the association between ACEs and adult depressive symptoms, and DunedinPoAm38 explained between 2 and 7% of the association between ACEs and adult depressive symptoms. Findings indicate accelerated aging, as measured by GrimAge and DunedinPoAm38, is associated with ACEs and with depressive symptoms in older Americans. Findings also show these epigenetic aging measures mediate a portion of the association between ACEs and adult depressive symptoms. Epigenetic aging may represent a physiological mechanism underlying the link between early life adversity and adult depression. Weight maintenance and substance use are potentially important areas for intervention.